Exploring the immunohistochemical profile of basosquamous carcinoma and its clinicopathological associations - Cemile Tuğba Altunel; Gonca Özgün; Arzu Karataş; Özlem Özen; Deniz Seçkin; Tülin Güleç; Deren Özcan (Turkderm Turkish Archives of Dermatology and Venereology)
Background and Design: Basosquamous carcinoma (BSC) is widely accepted as a basal cell carcinoma variant. Despite an unknown molecular pathogenesis, specific mutations are associated with its squamatization. Immunohistochemical studies offer insights into the tumor's genetic background. However, extensive investigations into its immunophenotype are lacking, and existing data present conflicting results. Materials and Methods: We analyzed the clinicopathological and immunohistochemical characteristics (Ber-Ep4, CK14, CK17, p53, p63, and Ki-67) of BSCs diagnosed between 1996 and 2017. Data were collected on patient demographics and tumor features, including location, ulceration rate, margin status, tissue invasion, mitotic activity, predominant cell type, and peritumoral lymphocytic infiltration. We explored the correlations among all parameters, including staining positivity rates and percentages, to understand their relationships better. Results: One hundred and four BSCs (68 males, mean age 67.99+-14.95) were included. The most common location was the nose. Ulceration rate and margin positivity were 70.2% and 22.1%, respectively. The cartilage, muscle, lymphovascular, and perineural invasion prevalences were 3.8%, 11.5%, 5.8%, and 5.8%, respectively. The mitotic activity was moderate-high in 68% of the tumors. The immunopositivity rates were; Ber-Ep4, 78.8%; CK14, 93.3%; CK17, 89.4%; p53, 80.8%; p63, 98.1%; Ki-67, 100%. Ulceration was associated with squamous cell predominance and CK14 positivity. The Ber-Ep4 intensity was higher in lesions with lymphovascular invasion. CK17, p53, and p63 expressions were higher on the scalp and face than in other sites. The p53 staining was associated with ulceration and peritumoral lymphocytic infiltration. The mitotic activity was correlated with the Ki-67 score. Conclusion: This study sheds light on the relationship between the clinicopathological and immunophenotypic characteristics of BSCs through an investigation of a large cohort. It has a high proliferation and ulceration rate. High margin positivity favors wide-excision margins. Long-term follow-up studies will clarify the prognostic significance of immunohistochemical markers mentioned in the study.